A cognitive behavioral intervention for college athletes with injuries - Podlog, L. W.; Heil, J.; Burns, R. D.; Bergeson, S.; Iriye, T.; Fawver, B.; Williams, A. M. (The Sport Psychologist, 2020)
The authors used a quasi-experimental design to examine the efficacy of a cognitive-behavioral-therapy (CBT) intervention for enhancing psychological well-being (positive and negative affect, vitality, self-esteem), rehabilitation adherence, and clinical rehabilitation outcomes (pain, physical function) in 16 NCAA (National Collegiate Athletics Association) Division I athletes experiencing a range of severe injuries. ANCOVAs, with adjusted baseline scores, revealed significant differences between the experimental and control groups for positive affect at rehabilitation midpoint (T2; adjusted mean difference (AMD) = 0.41, p = .04, n2 = .34) and return to play (T3; AMD = 0.67, p < .001, n2 = .70), negative affect at T3 (AMD = -0.81, p = .01, n2 = .47), and vitality at T2 (AMD = 0.99, p = .01, n2 = .48) and T3 (AMD = 1.08, p = .02, n2 = .33). Given decrements in emotional functioning after injury, the data support the use of CBT-based interventions for facilitating the emotional well-being of athletes with severe injuries.